The cat is out of the bag: How parasites know their hosts - English, Elizabeth D. (PLoS Biol, 2019)
Toxoplasma gondii is a remarkably successful protozoan parasite that infects a third of the human population, along with most mammals and birds. However, the sexual portion of the parasite’s life cycle is narrowly limited to cats. How parasites distinguish between hosts has long been a mystery. A new study reveals that Toxoplasma identifies cats based on a single fatty acid, linoleic acid. Experimental manipulation of fatty acid metabolism by drug treatment turns a mouse into a cat in the “eye” of the parasite. This new model enables genetic crosses of an important human pathogen without the use of companion animals and opens the door to future discovery.